2014
DOI: 10.1073/pnas.1322641111
|View full text |Cite
|
Sign up to set email alerts
|

Partial loss of TDP-43 function causes phenotypes of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurological disease that causes motor neuron degeneration, progressive motor dysfunction, paralysis, and death. Although multiple causes have been identified for this disease, >95% of ALS cases show aggregation of transactive response DNA binding protein (TDP-43) accompanied by its nuclear depletion. Therefore, the TDP-43 pathology may be a converging point in the pathogenesis that originates from various initial triggers. The aggregation is thought to result fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 81 publications
9
125
0
Order By: Relevance
“…Both TDP‐43 gain and loss of function have been proposed as possible crucial mechanisms in the pathogenesis of ALS, a devastating incurable neurodegenerative disorder, and both reduced TDP‐43 expression and TDP‐43 overexpression have detrimental effects in mice (Arnold et al , 2013; Yang et al , 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both TDP‐43 gain and loss of function have been proposed as possible crucial mechanisms in the pathogenesis of ALS, a devastating incurable neurodegenerative disorder, and both reduced TDP‐43 expression and TDP‐43 overexpression have detrimental effects in mice (Arnold et al , 2013; Yang et al , 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the main approach to studying LOF, by using null mice, has been hampered because TDP‐43 knockout (KO) causes very early embryonic lethality, and heterozygous mice have normal levels of TDP‐43 due to autoregulation (Kraemer et al , 2010; Sephton et al , 2010; Wu et al , 2010; Ricketts et al , 2014). However, conditional KO strategies and downregulation of TDP‐43 via siRNA suggest that acute TDP‐43 loss of function could lead to neurodegeneration (Chiang et al , 2010; Wu et al , 2012; Iguchi et al , 2013; Yang et al , 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Absence of TDP43 is lethal (25), and TDP43 knockdown recapitulates motor neuron loss in animal models (26). In addition, nuclear clearing of TDP43 is characteristic of ALS (27), and TDP43 overexpression triggers a reduction in endogenous (en)-TDP43 through autoregulation (15,28), suggesting that TDP43 overexpression may cause toxicity through a paradoxical reduction in en-TDP43.…”
mentioning
confidence: 99%
“…It has been reported that loss of TDP-43 function causes ALS. 7,36 To measure scalability with the dataset. we also ran TEtranscripts to compare running time of both methods.…”
Section: Datasetsmentioning
confidence: 99%